Trends in antipsychotic prescribing to children and adolescents in England: cohort study using 2000–19 primary care data. (February 2023) - Radojčić, Maja R; Pierce, Matthias; Hope, Holly; Senior, Morwenna; Taxiarchi, Vicky P; Trefan, Laszlo; Swift, Eleanor; Abel, Kathryn M
Summary: Background: The prescription of antipsychotics to children and adolescents has been increasing worldwide. We described up-to-date trends in antipsychotic prescribing and identified likely indications in a contemporary English cohort. Methods: We used a large primary care database, the Clinical Practice Research Datalink (CPRD) Aurum database, and we included all children and adolescents aged 3–18 years in the database and registered in England between Jan 1, 2000, and Dec 31, 2019, excluding those whose gender was recorded as indeterminate. Participants were followed up until the earliest of Dec 31, 2019, June 30 of the year they turned 18 years, their death, when they transferred from the primary care practice, or when the practice left the database. Data were not collected on ethnicity. We recorded antipsychotic prescriptions using the date a prescription was issued. As CPRD prescriptions are not linked to indications, we developed an algorithm to ascertain the most likely indication associated with participants' first antipsychotic prescription using clinical codes. We reported prescribing trends as annual period prevalence and the rate of first antipsychotic prescription, and we used joinpoint regression analysis to identify changes in the outcome trend. We stratified prevalence estimates by age group, gender, and Index of Multiple Deprivation quintiles, we reported frequencies of likely indications associated with incident prescriptions, and we explored clinical preference for typical versus atypical antipsychotics within deprivation quintiles. Findings: Between Jan 1, 2000, and Dec 31, 2019, we included 7 216 791 children and adolescents, of whom 3 480 730 (48·2%) were girls and 3 736 061 (51·8%) were boys, with a mean age at the start of follow-up of 7·3 years (SD 4·9; range 3–18). Median follow-up was 4·1 years (IQR 1·5–8·5). 19 496 (0·3%) individuals received 243 529 antipsychotic prescriptions over follow-up, including 225 710 (92·7%) atypical and 17 819 (7·3%) typical antipsychotic prescriptions. The annual period prevalence of antipsychotic prescriptions rose from 0·057% (95% CI 0·052–0·063%) in 2000 to 0·105% (0·100–0·111%) in 2019. From joinpoint analyses, the period prevalence of all antipsychotic prescriptions increased by an average of 3·3% per year (2·2–4·9%) and the rate of first prescriptions increased by 2·2% per year (1·7–2·7%). The most likely indications of the first identified antipsychotic prescriptions were for autism spectrum disorder (2477 [12·7%]), non-affective psychosis (1669 [8·6%]), anxiety disorders (1466 [7·5%]), ADHD (1391 [7·1%]), depression (1256 [6·4%]), and conduct disorders (1181 [6·1%]). Interpretation: The observed increase in antipsychotic prescriptions over 20 years results from the accumulation of repeated prescriptions to the same individuals combined with an increase in new prescriptions. These findings highlight the need for continued monitoring of trends in antipsychotic use and, although this was not examined in this paper, the findings highlights the need for better information about long-term antipsychotic safety. Funding: None.